2014
DOI: 10.1155/2014/430128
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and Psychological Symptoms in Poststroke Vascular Cognitive Impairment

Abstract: Background. Behavioural and psychological symptoms of dementia (BPSD) cause significant patient and caregiver morbidity in vascular cognitive impairment (VCI). Objectives. To study and compare the occurrence and severity of BPSD between multi-infarct dementia (MID), subcortical ischaemic vascular disease (SIVD), and strategic infarct subtypes of poststroke VCI and to evaluate the relationship of these symptoms with the severity of cognitive impairment. Methods. Sixty patients with poststroke VCI were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…Structural abnormality evidence has shown that the cortex thins in the parietal and temporal cortices as cognitive impairment worsens ( 4 ). Thus, this finding is compatible with previous studies, and the gradual progression of decreased nodal efficiency in parietal/temporal areas suggested that their lower capacity for information exchange with other nodes in the network presumably occurred in response to non-cognitive consequences such as apathy and slower motor function in patients with cognitive impairment caused by SIVD ( 3 , 41 , 42 ).…”
Section: Discussionsupporting
confidence: 92%
“…Structural abnormality evidence has shown that the cortex thins in the parietal and temporal cortices as cognitive impairment worsens ( 4 ). Thus, this finding is compatible with previous studies, and the gradual progression of decreased nodal efficiency in parietal/temporal areas suggested that their lower capacity for information exchange with other nodes in the network presumably occurred in response to non-cognitive consequences such as apathy and slower motor function in patients with cognitive impairment caused by SIVD ( 3 , 41 , 42 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, Thong et al (2014) found that the parietal and temporal cortices thin as cognitive impairment worsens in patients with cognitive impairment caused by SIVD, showing evidence of structural alterations in SIVCIND patients. Additionally, decreased nodal efficiency in the parietal/temporal areas suggests that their lower capacity for information exchange in the structural connectivity network is presumably associated with non-cognitive symptoms such as apathy and decreased motor function in SIVCIND patients (Gupta and Dasgupta, 2014).…”
Section: Decreased Nodal Efficiency In Sivcind Compared With Normal Cmentioning
confidence: 99%
“…Depression scales that have been shown to be sensitive to stroke-related mood disturbance include the Beck Depression Inventory and the Center for Epidemiologic Studies Depression Scale (CES-D) [126,127]. The Frontal Systems Behavior Scale (FrSBe) examines for the presence of dysexecutive, disinhibitive and apathetic behaviors both before and after a stroke, and has been found to be useful in this population [128], as has the Neuropsychiatric Inventory [129]. Both scales utilize a collateral source who knows the patient well as an informant for behavioral change and/or mood disturbance.…”
Section: Advances In Neuropsychological Protocolsmentioning
confidence: 99%